PEMBINAAN NARAPIDANA DALAM SISTEM PEMASYARAKATAN - Pettanase, Ismail (Solusi, 2019)
Penitentiary is stated as a system of guidance for lawbreakers and as an embodiment of justice which aims to achieve social reintegration or the restoration of the unity of relations between Prisoners and the community. Penitentiary in Indonesia has experienced significant changes, especially regarding the method of treating prisoners themselves. The idea of ​​the function of punishment according to Indonesia which adheres to the Pancasila ideology is no longer just deterrence but is also an attempt to rehabilitate and reintegrate socially Correctional Guidance (WBP) which has been established with a system of treatment of lawbreakers in Indonesia called the penal system